A Review of Water Balance Application in Water Supply. Issue 7 (1st July 2015) - Klingel, Philipp; Knobloch, Axel
Abstract : Establishing a water balance is a precondition of efficient water loss management in water supply systems. In this article, the applicability of available standards and methods for establishing the water balance is reviewed on the basis of an evaluation of literature in the field. In principle, establishing the water balance is made straightforward by measuring, estimating, and calculating the components of the water balance. However, water balances are often established that do not cover all components or are based on rough estimates. In most cases, water balances are determined for a whole network, not for zones, and only at long, mostly yearly, intervals, resulting in limited informational value of the findings. The main reasons for this seem to be the effort involved, the limited availability of data, and the lack of adequate methods for determining unmeasured components. This article concludes that there is a need for developing methods and tools to support water utilities in establishing complete, zonal water balances with reasonable effort.